Pelatihan Bimbingan Kelompok Berbasis Mindfulness mengurangi Kecemasan Karier Siswa SMA: Penelitian - Abdul Hadi; Anifa Tuzzuhroh Nurbaiti; Eka Aryani (Jurnal Pustaka Cendekia Pendidikan, 2026)
Guidance and Counseling teachers have a strategic role in helping students overcome career anxiety, but many BK teachers still lack the competency to implement Mindfulness-based group guidance services. Therefore, this community service activity aims to improve the competence of BK teachers in implementing Mindfulness-based group guidance as an effort to reduce career anxiety in high school students. The method used is participatory training which includes preparation, material delivery, demonstration, simulation, guided practice, evaluation, and follow-up. The activity participants were 15 Guidance and Counseling teachers from several high schools in Bantul Regency who were selected using a purposive sampling technique. Evaluation was carried out using Mindfulness-based group guidance skills instruments in the pretest and posttest to measure competency improvements after participating in the training. The training results showed an increase in BK teacher competency in all aspects measured. The average pretest result was 50.25%, increasing to 88.11% in the posttest, an increase of 37.86%. The highest improvement occurred in the aspect of Mindfulness technique mastery, while aspects of service preparation, group formation, group dynamics management, career discussion facilitation, counseling communication, and service closure also showed improvements, reaching the very good category. In addition to increased knowledge, participants were able to practice Mindfulness techniques in group guidance simulations according to the service stages that had been trained. This activity had a positive impact on improving the professional competence of guidance counselors in implementing Mindfulness-based group guidance.